STUDY OF CRITICAL POINTS IN THE DIFFERENTIAL CRYPTOANALYSIS OF S-BLOCKS IN HASHING ALGORITHM "HBC-256" (ADVANCED TECHNOLOGIES AND COMPUTER SCIENCE, 2022)
In this work described a differential cryptanalysis of the "HBC-256" algorithm one of the hashing algorithms developed at the Institute of Information and Computing Technologies of the RK MES CS, is provided. Taking into account the main properties of differential cryptanalysis and based on the conclusions of other scientific works, the situation of pairs of open and corresponding closed texts at critical points is studied. In the conclusion of the article, it is concluded that the S-boxes of the hashing algorithm are resistant to situations where it is possible to cause a collision through critical points in the table of differences.
Keywords: hash algorithms; requirements for hash algorithms; basic methods of cryptanalysis